Early Diagnosis of Interstitial Lung Disease - Anita Masniari Pulungan; Fanny Fachrucha (Respiratory Science, 2022)
Interstitial Lung Disease (ILD) includes more than 200 diseases that involve the interstitial lung. The diagnosis of ILD depends on the onset of symptoms, causes, and clinical manifestations. An anamnesis comprehensive and physical examination are essential in diagnosing ILD. In addition, laboratory tests are carried out in certain clinical conditions. The analysis of biomarkers in ILD is helpful for diagnosis, disease monitoring, and prediction of prognosis. Pulmonary function studies support the diagnosis of ILD and as a predictor of prognosis. High-resolution Computed Tomography (HRCT) is the main diagnostic procedure in ILD patients. In certain conditions, a lung biopsy may be considered. Multidisciplinary discussion (MDD) enhances accurate diagnosis. An accurate early diagnosis of ILD is necessary to ensure that patients receive optimal management, reduce the risk of developing pulmonary fibrosis and reduce the risk of death. Early diagnosis of ILD define as early identification of symptoms, laboratory and radiological findings at the early stage of the disease